Perfil de genótipos do vírus da hepatite C no Brasil entre indivíduos monoinfectados e coinfectados pelo HIV: um levantamento representativo do país - Nutini, Mariana Fernanda Rodrigues [UNIFESP] (2018)
Background: To receive treatment with Direct Antiviral Agents (DAAs), all HCV infected patients in Brazil need a genotype determination, which is provided by the Brazilian government soon after initial diagnosis as is the treatment. We assessed the HCV genotype profile according to Brazilian geographic region, gender, age and HIV coinfection. Methods: We assessed 29.071 samples from HCV infected patients subjected to HCV genotype (Abbott Real Time HCV Genotype) collected from March 2016 to March 2018. Samples which genotype assignment was unclear using qPCR, were subjected to sanger sequencing of either NS5B or 3´UTR regions. 12.336 randomly selected samples were tested for HIV coinfection using the EIA rapid test kit TR DPP HIV 1/2 BioManguinhos. Descriptive statistical analyses were performed using the R statistical system and language. Group comparisons of data was performed using chisquared tests. Results: Overall median age was 55 years old (from 18 to 90); 58,7% being males. Overall HCV genotype (G) distribution was 40.9% G1a, 30.2% G1b, 23.8% G3, 3.8% G2, 0.7% G4, 0.1% G5 and 0.6% with multiples genotypes. Prevalence of G1a was 44.4% among males and 35.8 among females, and G1b, and G2 were more prevalent in older ages than G1a and G3. G3 was more prevalent in the South region than in other Brazilian regions. Among 12.336 samples tested for HIV coinfection, 15% (95% CI = 14.3 – 15.4%) were HIV+, with a median age of 50 among coinfected patients as compared to 57 among monoinfected individuals. 71.1% of coinfected patients were male as compared to 58.7% of overall. The sample of HIV coinfection was: the South of Brazil (19.1%) South east (15.6%), Central (10.9%), Northeast (7.8%), and North (4.3%). Conclusion: This is a report of the genotype HCV that is truly representative of the entire country. High prevalence of G3 in the south of Brazil poses an extra challenge related to HCV disease progression and treatment response, as well as the higher prevalence of G1a especially among males, a genotype with lower genetic barrier to resistance to protease inhibitors.